A comparative study on tribological properties of leaf-surface waxes extracted from coastal and inland plants. Issue 4 (7th May 2019) - Xia, Yanqiu; Zhang, Wenyi; Cao, Zhengfeng; Feng, Xin
Abstract : Purpose: This paper aims to explore the leaf-surface wax as green lubricant additive and compare the tribological properties between coastal and inland leaf-surface waxes of the same species plant. Design/methodology/approach: The leaf-surface waxes were extracted from the leaves of Robinia pseudoacacia cv. Idaho and Populus nigra in coastal and inland areas, and then the compositions of the four kinds of leaf-surface waxes were characterized using a gas chromatography–mass spectrometry. The tribological properties of these leaf-surface waxes as lubricant additives in the base oil of synthetic ester (SE) were investigated by an MFT-R4000 reciprocating friction and wear tester. As well as the surface morphologies and chemical compositions of the wear scars were characterized by a scanning electron microscope and time-of-flight secondary ion mass spectrometry, respectively. Findings: The results indicate that all the leaf-surface waxes as additives can effectively improve the friction reduction and anti-wear performances of SE for steel–aluminum friction pairs. Therein, coastal leaf-surface waxes have better tribological performances than inland leaf-surface waxes, which are attributed to that the leaf-surface waxes extracted from coastal plants can form a better protective film on the worn surface throughout the friction process. Originality/value: This paper investigated a new kind of environmentally friendly lubricant additive and compared the tribological properties of the leaf-surface wax extracted from coastal and inland plants. The associated conclusions can provide a reference to explore the tribological performances of leaf-surface wax as green lubricant additive.